PBL Berbantu Media Audio Visual Terintegrasi Al-Quran : Pengaruhnya Terhadap Hasil Belajar Siswa Pada Materi Sistem Reproduksi - Sherly Aglillah; Ummi Nur Afinni Dwi Jayanti (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Background: Learning outcomes are the object of class evaluation as new abilities obtained by students after participating in the learning process. However, the facts on the ground show that high school students' learning outcomes in biology material are still low. Based on the results of interviews with State Madrasah Aliyah teachers in Serdang Bedagai, students' learning outcomes are generally low because they do not have a strong understanding of concepts, one of which is the material on the reproductive system. So we need a learning model that can help students understand the concept and can improve student learning outcomes. The purpose of this study was to see the effect of PBL learning with the help of Al-Quran Integrated Audio Visual Media on Student Learning Outcomes in Reproductive System Materials. Method: The population in this study were all class XI IPA Madrasah Aliyah Negeri in Serdang Bedagai which were taken using the saturated sampling technique. The type of research used is quantitative research, namely quasi-experimental research with nonrandomized control-group pretest-posttest research design. Conclusion: The results of data analysis obtained from the ancova test obtained a calculated F value of 8.394 with sig. 0.005, where 0.005 < = 0.05 which indicates that Ho is rejected and Ha is accepted. Using the PBL model assisted by the integrated audio-visual media of the Al-Quran on the material of the reproductive system.